Abuse of Position for Sexual Purposes: Array - Rusu, Ioana (Acta Universitatis Danubius. Juridica, 2020)
This paper includes a brief analysis of a new crime included in the Romanian Criminal Code. In the introductory part we have presented the incrimination referring to the need to incriminate it, as it is appreciated by the legislator. We have also examined, using recent doctrine, the pre-existing conditions of the crime, the constitutive content, as well as other relevant elements, the forms, modalities and sanctions provided by the law. Last but not least, we referred to some elements of similarity or difference from other crimes. The paper is part of a university course to be published in the near future. As designed, the paper can be useful to academia and practitioners in this field.